Motif Go Public, Herding, Ukuran Perusahaan, Dan Underpricing Pada Pasar Modal Indonesia - Fitri Ismiyanti; Rohmad Fuad Armansyah (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
Underpricing become a phenomenon which often occurs by companies during Initial Public Offering in every country in the world, which offering price lower than closing price on the first day trading on the stock exchange. According to Rock (1982), asymmetry information of an IPO company leads to underpricing phenomena, where the information according to the company are not evenly distributed among investors. This asymmetry information emerging distribution of uncertainty among investors that leads to underpricing. The objective of this research is to test the influence of motive of company going public, herding in stock market, and size of the company to the degree of underpricing using sample of 257 companies listed during year 1990 to June 2009 on the Indonesian Stock Exchange. Sample is taken by using purposive sampling with criteria as underpriced stocks and the stocks are not delisting overall from stock exchange. Data are analyzed using multiple regressions and path analysis to test the relation between motive of company going public, herding, and size of the company to the degree of underpricing. Pursuant to the analysis, motive of company going public and herding have positively influence on the degree of underpricing but statistically not significant. Size of the company which measure using total asset have negatively influence on the degree of underpricing and statistically significant on the first day trading on the stock exchange.